Composite ZnWO4 / BiOIO3 heterojunction photocatalyst as well as preparation method and application thereof
By designing a composite ZnWO4/BiOIO3 heterojunction photocatalyst, and using photocatalytic technology to decompose tetracycline under light irradiation, the problem of difficulty in dealing with tetracycline pollutants in the prior art is solved, and efficient and environmentally friendly pollutant removal is achieved.
Patent Information
- Application Number
- CN202411511474.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to efficiently treat tetracycline contaminants, especially in cases where poor biodegradability and cannot be removed by conventional treatment processes.
A composite ZnWO4/BiOIO3 heterojunction photocatalyst was designed, and the photocatalyst was prepared by hydrothermal reaction, and tetracycline was degraded by electron-hole pairs under light irradiation.
It has achieved efficient degradation of tetracycline in water, with good photocatalytic activity, chemical stability and reusability, reducing treatment costs and no secondary pollution.
Smart Images

Figure CN119386906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor photocatalytic materials and relates to advanced oxidation treatment of environmental pollutants. More specifically, it relates to a preparation method and application of a composite ZnWO4 / BiOIO3 heterojunction photocatalyst. Background Art
[0002] The discharge of various polluted waters has gradually begun to affect people's daily lives and has received widespread attention from the society. Antibiotics are overused in veterinary and clinical medicine, aquaculture, horticulture and agriculture, and are considered to be one of the emerging water environmental pollutants. Among the many antibiotics, tetracycline (TC) ranks second in the world in both production and usage, and is widely used to prevent and control a variety of human and animal diseases.
[0003] Currently, activated sludge method and anaerobic digestion method are commonly used to treat tetracycline wastewater, but they are usually subject to some limitations, such as high cost, low efficiency, and high condition requirements. In addition, due to the strong stability and poor biodegradability of TC, some conventional treatment processes cannot remove it from wastewater.
[0004] Photocatalytic technology has become an emerging hot technology for dealing with environmental pollution problems due to its advantages such as energy saving, high efficiency and safety. Compared with many traditional methods, semiconductor photocatalysis is considered to be a promising green technology for degrading organic pollutants. It can degrade pollutants into small molecules or mineralize them into CO2 and H2O under mild reaction conditions. Among the various photocatalysts used to remove environmentally difficult-to-degrade pollutants, semiconductor photocatalysis has the advantages of high oxidation intensity, complete mineralization of pollutants, and direct use of sunlight. In the reaction, the photocatalyst mainly produces electron-hole pairs under light irradiation. The separation and transmission of photoelectrons and holes lead to the generation of active substances, achieving the effect of degrading organic pollutants.
[0005] Zinc tungstate (ZnWO4) is a transition metal tungstate nanomaterial that has excellent properties for decomposing organic pollutants in water under ultraviolet light and is often used in industrial development applications. Bismuth iodate (BiOIO3) has strong oxidizing ability and has excellent photocatalytic activity for the degradation of organic pollutants under ultraviolet light.
[0006] The present invention will develop a new type of photocatalyst and combine it with photocatalytic technology to treat antibiotics such as tetracycline pollutants. Summary of the invention
[0007] In view of the problems existing in the above-mentioned prior art, in order to solve the problem that the prior art solutions are difficult to treat tetracycline pollutants, the purpose of the present invention is to design and provide a composite ZnWO4 / BiOIO3 heterojunction photocatalyst with high degradation efficiency, strong reusability, simple operation and good practicality, which can effectively treat tetracycline pollutants in water. The ZnWO4 / BiOIO3 heterojunction photocatalyst exhibits good photocatalytic activity and has high electrical conductivity, chemical stability and optical transparency.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] On the one hand, the present invention provides a composite ZnWO4 / BiOIO3 heterojunction photocatalyst, wherein the photocatalyst is a heterojunction material composed of ZnWO4 and BiOIO3.
[0010] In a second aspect, the present invention provides a method for preparing a composite ZnWO4 / BiOIO3 heterojunction photocatalyst, comprising the following steps:
[0011] Weigh an aqueous solution of bismuth nitrate pentahydrate, add potassium iodate under continuous stirring, stir evenly, add zinc tungstate, continue stirring, and carry out hydrothermal reaction. After the reaction is completed, cool to room temperature, wash, dry, and grind to obtain a ZnWO4 / BiOIO3 heterojunction photocatalyst.
[0012] The preparation method, the specific preparation method of the zinc tungstate is: weigh zinc nitrate hexahydrate and sodium tungstate dihydrate, add water and stir evenly, carry out hydrothermal reaction, cool to room temperature, wash, dry, grind, and obtain zinc tungstate.
[0013] In the preparation method, the molar ratio of zinc nitrate hexahydrate to sodium tungstate dihydrate is 1:2 to 3:2;
[0014] The conditions of the hydrothermal reaction are: temperature 170-190°C, time 14-16h;
[0015] The washing conditions are: washing with deionized water and anhydrous ethanol alternately, and the number of washing times is 3 to 6 times;
[0016] The drying temperature is 50-90°C.
[0017] In the preparation method, the molar ratio of the aqueous solution of bismuth nitrate pentahydrate to potassium iodate is 1:2 to 3:2.
[0018] The preparation method, the conditions of the hydrothermal reaction are: temperature 120-140°C, time 5-7h.
[0019] The preparation method, the drying condition is: temperature 50 ~ 90 ℃.
[0020] In the preparation method, the mass ratio of the aqueous solution of bismuth nitrate pentahydrate to zinc tungstate is 20:1 to 5:1.
[0021] The composite ZnWO4 / BiOIO3 heterojunction photocatalyst or the ZnWO4 / BiOIO3 heterojunction photocatalyst obtained by the preparation method is used in photocatalytic degradation of antibiotics in water. The prepared heterojunction material is mixed with the tetracycline wastewater to be treated, stirred in a dark environment, and after reaching adsorption-desorption equilibrium, it is transferred to simulated sunlight conditions for photocatalytic reaction to achieve the removal of tetracycline in the wastewater.
[0022] In the application, the antibiotic is tetracycline.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The ZnWO4 / BiOIO3 heterojunction photocatalyst of the present invention generates electron-hole pairs under light irradiation, and the separation and transmission of photoelectrons and holes lead to the generation of active substances, thereby achieving the effect of degrading organic pollutants.
[0025] 2. The raw materials used in this application are zinc nitrate, sodium tungstate and bismuth nitrate, etc. These materials are cheap and easy to obtain. In BiOIO3, the unique 2D layered structure and asymmetric crystal arrangement produce an internal polarization electric field, which improves the separation efficiency of photoexcited charges. ZnWO4 has high chemical stability and reactivity, high average refractive index, excellent light output characteristics, molecular and electronic multifunctionality, high catalytic activity, short decay time and high X-ray absorption coefficient.
[0026] 3. The method of the present invention is simple, easy to operate, greatly reduces the cost, has high purity of the manufacturing material, and is reusable, and has extremely high application value.
[0027] 4. The present invention utilizes solar energy as a clean and renewable energy source, and there is no secondary pollution after treatment. It can not only degrade organic matter into non-toxic and harmless small molecules, but also maintain ecological balance, which is beneficial to the protection of the ecological environment and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD diagrams of ZnWO4 prepared in Comparative Example 1, BiOIO3 prepared in Comparative Example 2, and composite ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in Examples 1, 2, and 3;
[0029] Figure 2The SEM images and EDS images of ZnWO4 prepared in Comparative Example 1, BiOIO3 prepared in Comparative Example 2, and the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material prepared in Example 2, wherein a is the SEM image of the ZnWO4 material, b is the SEM image of the BiOIO3 material, and c is the SEM image of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material prepared in Example 2;
[0030] Figure 3 The degradation effect diagram of tetracycline by ZnWO4 prepared in comparative example 1, BiOIO3 prepared in comparative example 2, and composite ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in examples 1, 2, and 3 under different photocatalytic treatment time conditions;
[0031] Figure 4 It is a kinetic curve diagram of tetracycline degradation by ZnWO4 prepared in Comparative Example 1, BiOIO3 prepared in Comparative Example 2, and composite ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in Examples 1, 2, and 3;
[0032] Figure 5 This is a diagram showing the degradation effect of tetracycline on the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material prepared in Example 2 under different water source environments. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments. It is particularly noted that if no specific conditions are specified in the following embodiments, the reactions are carried out under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments are commercially available and are analytically pure.
[0034] Embodiment 1:
[0035] A method for preparing a composite ZnWO4 / BiOIO3 heterojunction photocatalytic material comprises the following steps:
[0036] (1) Place 2 mmol of zinc nitrate hexahydrate and 2 mmol of sodium tungstate dihydrate in a 50 mL beaker, add 25 mL of deionized water, and place the beaker on a magnetic stirrer for 30 minutes. Then transfer the obtained uniform solution to a 50 mL polytetrafluoroethylene-lined reactor, place it in an oven, and react at 180°C for 15 hours. After the reaction is completed, cool to room temperature, take out the reactant, collect the obtained precipitate by centrifugation, wash it alternately with deionized water and anhydrous ethanol for 3 times, and place the solid obtained after washing in an oven, heat it at 60°C for 12 hours, and grind the reactant obtained after drying to obtain zinc tungstate (ZnWO4).
[0037] (2) 1 mmol of bismuth nitrate pentahydrate was placed in a 50 mL beaker, 30 mL of deionized water was added, and the beaker was placed on a magnetic stirrer and stirred for 30 minutes to obtain a uniform solution. Then, under continuous stirring, 1 mmol of potassium iodate was added, and the mixture was stirred on a magnetic stirrer for 60 minutes to make it uniformly distributed. Then, 0.015 g of the zinc tungstate material prepared in step (1) was added thereto, and the stirring was continued for 3 hours. The mixed uniform solution was then transferred to a 60 mL reactor, placed in an oven, and reacted at 130° C. for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, the obtained precipitate was centrifuged, and washed alternately with deionized water and anhydrous ethanol for 3 times, and the solid obtained after washing was placed in an oven and dried at 60° C. for 12 hours. The reactant obtained after drying was ground to obtain a ZnWO4 / BiOIO3 heterojunction photocatalyst material (referred to as A1).
[0038] The XRD patterns of ZnWO4 prepared in Comparative Example 1, BiOIO3 prepared in Comparative Example 2, and ZnWO4 / BiOIO3 heterojunction photocatalytic materials (A1, A2, A3) prepared in Examples 1, 2, and 3 are shown in FIG. Figure 1 As shown in the results, the diffraction peak of ZnWO4 is basically consistent with the standard card (PDF#15-0774), and there is no diffraction peak of any impurity peak, indicating that the obtained sample is ZnWO4. The diffraction peak of BiOIO3 is basically consistent with the standard card (PDF#26-2019), without any impurity peak, indicating that the obtained sample is BiOIO3. Figure 1 Curves A1, A2, and A3 in the figure are the XRD spectra of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in Examples 1, 2, and 3, respectively. It can be seen that as the doping ratio of ZnWO4 increases, the crystallinity of BiOIO3 also changes, indicating that ZnWO4 and BiOIO3 are well composited together.
[0039] Embodiment 2:
[0040] The same preparation method as in Example 1 is used, except that the mass of zinc tungstate in step (2) is 0.022 g, so that the mass ratio of ZnWO4 to BiOIO3 is 7:100, and finally a ZnWO4 / BiOIO3 heterojunction photocatalyst material (denoted by A2) is obtained.
[0041] The SEM and EDS images of the ZnWO4 prepared in Comparative Example 1, the BiOIO3 prepared in Comparative Example 2, and the ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in Example 2 are shown in FIG. Figure 2As shown in the figure, it can be seen that the ZnWO4 nanoparticles of the ZnWO4 / BiOIO3 heterojunction photocatalytic material prepared in Example 2 grow on the surface of the BiOIO3 nanosheets and are evenly distributed. The successful construction of this heterojunction is more likely to increase the specific surface area of the material, thereby achieving the effect of enhancing the photocatalytic degradation ability. Figure 2 From the EDS image, we can see that the Zn, W, O, Bi, and I elements are evenly distributed on the material, which further demonstrates the successful synthesis of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material.
[0042] Embodiment 3:
[0043] The same preparation method as in Example 1 is used, except that the mass of zinc tungstate in step (2) is 0.031 g, so that the mass ratio of ZnWO4 to BiOIO3 is 1:10, and finally a ZnWO4 / BiOIO3 heterojunction photocatalyst material (denoted by A3) is obtained.
[0044] Comparative Example 1:
[0045] 2mmol of zinc nitrate hexahydrate and sodium tungstate dihydrate were placed in a 50mL beaker, 25mL of deionized water was added, and the beaker was placed on a magnetic stirrer for 30 minutes. Then the obtained uniform solution was transferred to a 50mL polytetrafluoroethylene-lined reactor, placed in an oven, and reacted at 180°C for 15h. After the reaction was completed, it was cooled to room temperature, the reactant was taken out and the obtained precipitate was collected by centrifugation, and washed alternately with deionized water and anhydrous ethanol for 3 times, and the solid obtained after washing was placed in an oven and heated at 60°C for 12h. The reactant obtained after drying was ground to obtain zinc tungstate (ZnWO4).
[0046] Comparative Example 2:
[0047] Place 1 mmol of bismuth nitrate pentahydrate in a 50 mL beaker, add 30 mL of deionized water, and place the beaker on a magnetic stirrer and stir for 30 minutes to obtain a uniform solution. Then, under continuous stirring, add 1 mmol of potassium iodate, and continue stirring on a magnetic stirrer for 60 minutes to make it evenly distributed. Then transfer the obtained mixed uniform solution to a 100 mL stainless steel reactor, place it in an oven, and react at 130 ° C for 6 hours. After the reaction is completed, cool to room temperature, centrifuge the obtained precipitate, and wash it alternately with deionized water and anhydrous ethanol for 3 times, and place the solid obtained after washing in an oven, dry it at 60 ° C for 12 hours, and grind the reactant obtained after drying to obtain bismuth iodate (BiOIO3) monomer material.
[0048] Embodiment 4:
[0049] The degradation efficiency of the photocatalyst material of the present invention on tetracycline is tested by a method comprising the following steps:
[0050] Weigh the zinc tungstate material prepared in Comparative Example 1, the BiOIO3 material prepared in Comparative Example 2, and the ZnWO4 / BiOIO3 heterojunction photocatalytic materials (A1, A2, A3) obtained in Examples 1-3, 35 mg each, and add them to 50 mL of tetracycline aqueous solution, wherein the tetracycline concentration is 20 mg / L. The mixed solution of the catalyst and the tetracycline solution was magnetically stirred for 30 minutes under dark conditions. After reaching the adsorption-desorption equilibrium, the photocatalytic reaction was carried out under sunlight simulated by a xenon lamp, and samples were taken every 20 minutes for 100 minutes of photocatalytic reaction. Finally, the tetracycline concentration after photocatalysis was analyzed by infrared analysis of the water sample taken.
[0051] Blank group: Take 50 mL of tetracycline solution with a concentration of 20 mg / L, without adding any catalyst material, and treat it under the same experimental conditions as the group with catalyst added, as a control.
[0052] The degradation effect of the zinc tungstate material prepared in Comparative Example 1, the BiOIO3 material prepared in Comparative Example 2, and the ZnWO4 / BiOIO3 heterojunction photocatalytic materials (A1, A2, A3) obtained in Examples 1-3 on tetracycline under different photocatalytic treatment time conditions is shown in the figure. Figure 3 As shown. During the photocatalytic reaction, samples were taken every 20 minutes, and the concentration changes were measured using a UV-visible photometer to obtain the degradation efficiency of tetracycline by different photocatalysts. Figure 3 It can be seen that the composite ZnWO4 / BiOIO3 heterojunction photocatalytic materials prepared in Examples 1-3 of the present invention have a good degradation effect on tetracycline, and the degradation effect of the photocatalytic material prepared in Example 2 is the best.
[0053] The kinetic curves of tetracycline degradation by the zinc tungstate material prepared in Comparative Example 1, the BiOIO3 material prepared in Comparative Example 2, and the ZnWO4 / BiOIO3 heterojunction photocatalytic materials (A1, A2, A3) obtained in Examples 1-3 are shown in FIG. Figure 4 As shown, it can be seen that the degradation rate of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 is the highest.
[0054] Embodiment 5:
[0055] The degradation efficiency of tetracycline by the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 in different water bodies was investigated:
[0056] Group 1: Weigh 35 mg of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 and add it to 50 mL of deionized water with a tetracycline concentration of 20 mg / L. The mixed solution of the catalyst and the tetracycline solution is magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction is carried out under a xenon lamp simulating sunlight, and samples are taken every 20 minutes for a photocatalytic reaction of 100 minutes. Finally, the tetracycline concentration after photocatalysis is analyzed by infrared analysis of the water samples.
[0057] Group 2: Weigh 35 mg of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 and add it to 50 mL of lake water with a tetracycline concentration of 20 mg / L. The mixed solution of the catalyst and the tetracycline solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under a xenon lamp simulating sunlight, and samples were taken every 20 minutes for a photocatalytic reaction of 100 minutes. Finally, the tetracycline concentration of the water samples was tested.
[0058] The third group: 35 mg of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 was weighed and added to 50 mL of tap water with a tetracycline concentration of 20 mg / L. The mixed solution of the catalyst and the tetracycline solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under a xenon lamp simulating sunlight, and samples were taken every 20 minutes for a photocatalytic reaction of 100 minutes. Finally, the tetracycline concentration of the water samples was tested.
[0059] Group 4: 35 mg of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 was weighed and added to 50 mL of rainwater with a tetracycline concentration of 20 mg / L. The mixed solution of the catalyst and the tetracycline solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under a xenon lamp simulating sunlight, and samples were taken every 20 minutes for a photocatalytic reaction of 100 minutes. Finally, the tetracycline concentration of the water samples was tested.
[0060] The degradation effect of the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 on tetracycline in different water source environments including deionized water, lake water, tap water and rainwater is as follows: Figure 5 As shown in the figure, the ordinate is the ratio of the concentration of tetracycline after degradation to its initial concentration at a certain moment. Figure 5It can be seen that the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material (A2) prepared in Example 2 of the present invention has efficient photocatalytic performance for tetracycline in deionized water, rainwater, lake water, and tap water environments, among which the degradation rate in deionized water is the highest and the degradation rate in rainwater is the lowest, which may be due to the weak acidity of rainwater and the high COD content. The composite heterojunction photocatalyst can achieve effective degradation of tetracycline in different water environments, indicating that the composite ZnWO4 / BiOIO3 heterojunction photocatalytic material of the present invention has good practical usability and feasibility, and has broad application prospects.
[0061] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A composite ZnWO4 / BiOIO3 heterojunction photocatalyst, characterized in that: The photocatalyst is a heterojunction material composed of ZnWO4 and BiOIO3.
2. The method for preparing a composite ZnWO4 / BiOIO3 heterojunction photocatalyst according to claim 1, characterized in that: The following steps are involved: Weigh an aqueous solution of bismuth nitrate pentahydrate, add potassium iodate under continuous stirring, stir evenly, add zinc tungstate, continue stirring, and carry out hydrothermal reaction. After the reaction is completed, cool to room temperature, wash, dry, and grind to obtain a ZnWO4 / BiOIO3 heterojunction photocatalyst.
3. The preparation method according to claim 2, characterized in that: The specific preparation method of the zinc tungstate is: weigh zinc nitrate hexahydrate and sodium tungstate dihydrate, add water and stir evenly, carry out hydrothermal reaction, cool to room temperature, wash, dry, grind, and obtain zinc tungstate.
4. The preparation method according to claim 3, characterized in that: The molar ratio of zinc nitrate hexahydrate to sodium tungstate dihydrate is 1:2 to 3:2; The conditions of the hydrothermal reaction are: temperature 170-190°C, time 14-16h; The washing conditions are: washing with deionized water and anhydrous ethanol alternately, and the number of washing times is 3 to 6 times; The drying temperature is 50-90°C.
5. The preparation method according to claim 2, characterized in that: The molar ratio of the aqueous solution of bismuth nitrate pentahydrate to potassium iodate is 1:2 to 3:
2.
6. The preparation method according to claim 2, characterized in that: The conditions of the hydrothermal reaction are: temperature 120-140° C., time 5-7 h.
7. The preparation method according to claim 2, characterized in that: The drying conditions are: temperature 50-90°C.
8. The preparation method according to claim 2, characterized in that: The mass ratio of the aqueous solution of bismuth nitrate pentahydrate to zinc tungstate is 20:1 to 5:
1.
9. Use of the composite ZnWO4 / BiOIO3 heterojunction photocatalyst as claimed in claim 1, or the ZnWO4 / BiOIO3 heterojunction photocatalyst obtained by the preparation method as claimed in claims 2-8 in photocatalytic degradation of antibiotics in water.
10. The use according to claim 9, characterized in that The antibiotic is tetracycline.
Citation Information
Patent Citations
Zinc tungstate / bismuth oxyiodide heterojunction visible light photocatalysis material and fabrication method thereof
CN103007971A
Preparation method of modified flower-shaped bismuth oxyiodide photocatalyst
CN110433830A
Preparation method and application of bismuth tungstate doped bismuth oxyiodate heterojunction photocatalyst
CN117380228A